Assessing Strategies in EFL Classes During the Onsite Transition Period at a Senior High School in Mengwi - I Gusti Ayu Komang Putri Tri Wahyuni; Luh Putu Artini; Luh Gede Eka Wahyuni (Acitya: Journal of Teaching and Education, 2023)
During teachers' adaptation to online learning, the Covid-19 case has shown a decline indicating that general health conditions are starting to improve. This has encouraged the government to re-implement face-to-face learning while still paying attention to health protocols. During the transition from online to onsite learning, teachers must adjust their strategy, especially the assessment strategy, because onsite learning differs from pre-pandemic onsite learning. Therefore, this research aims to describe the assessment strategies applied by teachers during the transition period. This research is descriptive qualitative research. Researchers used observation sheets, and interviews as instruments, and data were analyzed using the Miles and Huberman models. The findings from this study are that teachers use an assessment strategy based on three assessment approaches according to the 2013 curriculum: assessment as learning, assessment for learning, and assessment of learning. However, in this transitional period, teachers are considered to need to improve in applying technology to assessment. Besides that, the strategies used by teachers also tend to be monotonous. The results of this study are expected to be a reflection for teachers in determining the right strategy in the transition from online to onsite learning.